Chemical modification of graphene for atomic-scale catalyst supports. (1st December 2022) - Kunisada, Yuji; Sakaguchi, Norihito
Abstract: One promising way to reduce the use of noble metal catalysts is to use extremely fine particle catalysts, such as subnanoclusters and single-atom catalysts. For practical use, suppression of diffusion and agglomeration of catalysts are needed. Heteroatom-doped graphene, which has high specific surface area, high chemical and mechanical stabilities, high electrical and thermal conductivities, and contains anchoring sites for catalysts, is promising catalyst support. Heteroatom-doped graphene can widely control the support effects. This review summarizes recent dopant structure characterization using spectroscopy and density functional theory calculations. The distribution of highly-dispersed metal catalysts and their diffusion properties are discussed. In addition, The effects of environmental conditions on catalyst dynamic behaviors are introduced. Finally, the outlook of heteroatom-doped graphene and new two-dimensional material supports is discussed.